Yōkai and “Old Japan” in Lore, Art, and Film: Studying Japan through Studying Yōkai - Joyce Mihara Boss (Education About Asia, 2026)
Yōkai, understood broadly as supernatural beings or forces, are rooted in elements of traditional Japanese beliefs, practices, and lore. In the modern (post-Meiji) era, and especially in recent decades, yōkai often function as nostalgic iconographic callbacks to an “Old Japan,” a world which is regarded as already lost or actively fading in a modern world which privileges efficiency, dominance, and a rather humorless rationalism. While stereotypical assumptions and depictions of Old Japan can be problematic, the elements of the traditional Japanese past as represented in yōkai texts, particularly recent films, can serve as useful wayfinders in identifying elements that were, and are, important in various facets of traditional Japan. This article discusses three yōkai-related films in which specific details invoking and portraying Old Japan—in this instance, agrarian landscapes, community rituals, and social relationships—can be identified and analyzed: My Neighbor Totoro (dir. Miyazaki Hayao, 1988); The Great Yōkai War (dir. Miike Takashi, 2005); and Destiny: The Tale of Kamakura (dir. Yamazaki Takashi, 2017). These films serve as examples of the ways in which yōkai—as characters, story elements, and metaphors—can serve as evocative guides within various areas of Japan studies.
Keywords: japan; yokai; monsters; folklore; supernatural; storytelling; Totoro